2014
DOI: 10.1007/s12011-014-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Riboflavin and Selenium on Brain Microsomal Ca2+-ATPase and Oxidative Damage Caused by Glyceryl Trinitrate in a Rat Headache Model

Abstract: Migraine headaches are considered to be associated with increased mitochondrial energy metabolism. Mitochondrial oxidative stress is also important in migraine headache pathophysiology although riboflavin and selenium (Se) induced a modulator role on mitochondrial oxidative stress in the brain. The current study aimed to determine the effects of Se with/without riboflavin on the microsomal membrane Ca(2+)-ATPase (MMCA), lipid peroxidation, antioxidant, and electroencephalography (EEG) values in glyceryl trinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 44 publications
(97 reference statements)
0
26
0
Order By: Relevance
“…RF and selenium (SE) can decrease lipid peroxidation (LP) levels and increase glutathione and reduced glutathione levels in microsomal brains. The co-administration of RF and vitamin E induced a decrease in calcium and a decrease in brain and microsomal lipid peroxidation levels [19,20]. The brain and microsomal lipid peroxidation levels (LP) have been found to be higher in the GTN-induced rats with migraine headaches compared to healthy rats [19]; whereas SE orally pre-treated rats with or without RF were protected against GTN-induced brain oxidative toxicity, by inhibiting free radicals and MMCA activity and supporting the antioxidant effect of RF [19].…”
Section: Neuropathymentioning
confidence: 93%
See 2 more Smart Citations
“…RF and selenium (SE) can decrease lipid peroxidation (LP) levels and increase glutathione and reduced glutathione levels in microsomal brains. The co-administration of RF and vitamin E induced a decrease in calcium and a decrease in brain and microsomal lipid peroxidation levels [19,20]. The brain and microsomal lipid peroxidation levels (LP) have been found to be higher in the GTN-induced rats with migraine headaches compared to healthy rats [19]; whereas SE orally pre-treated rats with or without RF were protected against GTN-induced brain oxidative toxicity, by inhibiting free radicals and MMCA activity and supporting the antioxidant effect of RF [19].…”
Section: Neuropathymentioning
confidence: 93%
“…The co-administration of RF and vitamin E induced a decrease in calcium and a decrease in brain and microsomal lipid peroxidation levels [19,20]. The brain and microsomal lipid peroxidation levels (LP) have been found to be higher in the GTN-induced rats with migraine headaches compared to healthy rats [19]; whereas SE orally pre-treated rats with or without RF were protected against GTN-induced brain oxidative toxicity, by inhibiting free radicals and MMCA activity and supporting the antioxidant effect of RF [19]. It has been demonstrated that RF plays a protective role in a time-and dose-dependent manner against excitotoxicity of cerebellar granule neurons induced by glutamate/NMDA in C57/B strain mice [21].…”
Section: Neuropathymentioning
confidence: 93%
See 1 more Smart Citation
“…53 Selenium treatment as organic selenomethionine and inorganic SeO 3 2À resulted in a similar increased activity of antioxidant enzymes, scavenging of reactive oxygen species (ROS) and reduced protein carbonyl content of patulin-induced brain damaged rats, 54 and reduced the pro-oxidant effects of glyceryl trinitrate in a rat model of migraine headaches. 55 Administration of SeO 3 2À to suckling pups whose dams had methimazole-induced hypothyroidism decreased total oxidant status and reduced degenerative changes in the granular cell layer of the dental gyrus, 56 and increased levels of brain-derived neurothophic factor (BDNF) in the hippocampus and cerebellum of both hypothyroid and control groups. 57 In a rat model of postnatal protein malnutrition oral Se and zinc (Zn) supplementation increased not only antioxidant enzyme activity, but also corrected the neurobehavioral deficits caused by a protein-deficient diet.…”
Section: Metallomicsmentioning
confidence: 99%
“…The dosage was determined according to Ethical Committee of Suleyman Demirel University and literature (Nazıroğlu et al . ). Ketamine was purchased from Pfizer, Istanbul, Turkey, and xylazine was purchased from Egevet, Izmir, Turkey.…”
Section: Methodsmentioning
confidence: 97%